2017
DOI: 10.1177/2192568217701097
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Fractures and Associated Injuries

Abstract: Study Design:Literature review.Objective:The aim of this review is to describe the injuries associated with sacral fractures and to analyze their impact on patient outcome.Methods:A comprehensive narrative review of the literature was performed to identify the injuries associated with sacral fractures.Results:Sacral fractures are uncommon injuries that result from high-energy trauma, and that, due to their rarity, are frequently underdiagnosed and mistreated. Only 5% of sacral fractures occur in isolation. Inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 43 publications
(68 reference statements)
0
43
0
5
Order By: Relevance
“…In a study on unstable sacral fractures, Rodrigues-Pinto et al reported that 40.6% of the 32 patients had upper limb involvement, 13 while only 5.4% of those with sacral fractures had some extent of upper limb injuries. Although our study did not examine the difference between levels of cervical spine injury and neurological deficits, a Scandinavian study found that subaxial injuries were more likely to have neurological deficits than C0-C2 injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on unstable sacral fractures, Rodrigues-Pinto et al reported that 40.6% of the 32 patients had upper limb involvement, 13 while only 5.4% of those with sacral fractures had some extent of upper limb injuries. Although our study did not examine the difference between levels of cervical spine injury and neurological deficits, a Scandinavian study found that subaxial injuries were more likely to have neurological deficits than C0-C2 injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The complication of sacral fracture is not limited to only urinary tract injury, but it also associated with neurological injuries (Rodrigues-Pinto et al 2017) and this includes loss of ankle reflex, the external anal and bladder sphincter, and parasympathetic innervation of the detrusor muscle of the bladder which are all contributed by sacral plexus (Chiaruttini 1987). Fortunately, there was no neurological deficit in this case.…”
Section: Besidesmentioning
confidence: 70%
“…The mechanism of injury might be able to give some clue for the attending physician to suspect the possibility of sacral fracture. However, it is still frequently missed in the primary survey due to the rarity of occurrence (Rodrigues-Pinto et al 2017). In this patient, the index of suspicion of the possibility of sacral fracture was low because patient could not remember the exact mechanism of injury.…”
Section: Discussionmentioning
confidence: 83%
“…The ventral rami of S2, S3, and S4 are distributed to the pudendal nerve, which provides sensation to the skin around the anus and perineum, and motor control of the urethral sphincter and external anal sphincter [7]. S2 to S4 nerve roots are also involved in the parasympathetic control of coordinated function of the bladder and rectum and sympathetic control of urethral and anal sphincter contraction [8]. In the present case, instability in fractured neural foramina bilaterally was considered to lead to damage of the sacral roots that resulted in neurological deficits.…”
Section: Discussionmentioning
confidence: 99%